2019
DOI: 10.3390/ijms20071765
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Characterization, Evolution, and Expression Profiling of VQ Gene Family in Response to Phytohormone Treatments and Abiotic Stress in Eucalyptus grandis

Abstract: VQ genes play important roles in plant development, growth, and stress responses. However, little information regarding the functions of VQ genes is available for Eucalyptus grandis. In our study, genome-wide characterization and identification of VQ genes were performed in E. grandis. Results showed that 27 VQ genes, which divided into seven sub-families (I–VII), were found, and all but two VQ genes showed no intron by gene structure and conserved motif analysis. To further identify the function of EgrVQ prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
0
11
0
1
Order By: Relevance
“…In this study, we found that six NtVQs (NtVQ17, NtVQ23, NtVQ43, NtVQ44, NtVQ47, and NtVQ49) significantly upregulated at both 3 h and 24 h, and six NtVQs (NtVQ35, NtVQ48, NtVQ50, NtVQ51, NtVQ52, and NtVQ57) significantly downregulated at both 3 h and 24 h (Figures 1 and 4, Supplementary Figure S2, Table S5). Previously, it was reported that only three genes showed upregulation and multiple OsVQ genes showed downregulation after 12 h under ABA treatment in rice [12], whereas most of the VQ genes were upregulated when exposed to ABA treatment in Moso bamboo [18] and Eucalyptus grandis [60]. These different expression patterns of the VQ gene family upon ABA treatment in different plant species may indicate diverse functions of VQ genes towards stress.…”
Section: Expression Analysis Of Ntvq Genes In Response To Biotic and mentioning
confidence: 91%
“…In this study, we found that six NtVQs (NtVQ17, NtVQ23, NtVQ43, NtVQ44, NtVQ47, and NtVQ49) significantly upregulated at both 3 h and 24 h, and six NtVQs (NtVQ35, NtVQ48, NtVQ50, NtVQ51, NtVQ52, and NtVQ57) significantly downregulated at both 3 h and 24 h (Figures 1 and 4, Supplementary Figure S2, Table S5). Previously, it was reported that only three genes showed upregulation and multiple OsVQ genes showed downregulation after 12 h under ABA treatment in rice [12], whereas most of the VQ genes were upregulated when exposed to ABA treatment in Moso bamboo [18] and Eucalyptus grandis [60]. These different expression patterns of the VQ gene family upon ABA treatment in different plant species may indicate diverse functions of VQ genes towards stress.…”
Section: Expression Analysis Of Ntvq Genes In Response To Biotic and mentioning
confidence: 91%
“…S 4 ). The ABRE elements involved in ABA signaling and osmotic stress [ 41 – 43 ] appeared in all DHN gene promoter regions, and the DRE1/DRE core being abundantly present in 45 DHN promoter regions ensured that DHN gene expression was regulated in response to drought stress [ 44 ]. MeJA-RE appeared in the promoter regions of 41 DHN genes, followed by TC-rich repeats and LTR being present in 21.…”
Section: Resultsmentioning
confidence: 99%
“…ABRE elements broadly involving ABA signaling and osmotic stress [36-38], it was appeared in all DHN gene promoter regions. DRE1/DRE core appears in 45 DHN promoter regions, and the abundance of these cis-acting elements ensured that gene expression is regulated in response to drought stress [39]. MeJA-RE appeared in the promoter regions of 41 DHN genes, followed by TC-rich repeats and LTR, with a number of 21.…”
Section: Sequence Analysis and Re-annotation Of The Dhn Gene Familymentioning
confidence: 99%